Antibacterial, antifouling and highly corrosion-resistant functionalized ZIF-8 epoxy coating

By using functionalized ZIF-8 epoxy coating in the marine environment, encapsulate antibacterial agent and loading it on fluorinated graphene, the problem of poor long-term protection effect of epoxy coating on metal substrates in the prior art is solved, and a coating with high corrosion resistance and antibacterial and antifouling properties is achieved.

CN119775894APending Publication Date: 2025-04-08SICHUAN UNIVERSITY OF SCIENCE AND ENGINEERING
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411984103.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The modified epoxy coatings in the prior art have poor long-term protection effect on metal substrates in the marine environment, and it is difficult to effectively prevent biological fouling and microbial corrosion.

Method used

Using a functionalized ZIF-8 epoxy coating, an antibacterial agent is encapsulated in the porous structure of ZIF-8 and loaded on fluorinated graphene to form a coating with high corrosion resistance and antibacterial antifouling.

Benefits of technology

It significantly improves the antibacterial and antifouling properties and corrosion resistance of the coating, and can provide long-term metal matrix protection in complex marine environments, reducing biological fouling and microbial corrosion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775894A_ABST
    Figure CN119775894A_ABST
Patent Text Reader

Abstract

The invention discloses an antibacterial, antifouling and highly corrosion-resistant functionalized ZIF-8 epoxy coating, which is prepared by the following steps: fully stirring a functionalized ZIF-8 filler with epoxy resin and a diluent in a certain proportion, adding a proper amount of a curing agent, coating a metal matrix with the mixture, and drying to obtain the functionalized ZIF-8 epoxy coating. The coating provides a physical barrier for the metal matrix, enhances the protection capability for the metal matrix on the chemical level, and can keep long-term stability and reliability in a complex marine environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of heavy-duty anticorrosive coatings in marine environments, and in particular to a functionalized ZIF-8 epoxy coating that is antibacterial, antifouling and highly corrosion-resistant. Background Art

[0002] Microbial corrosion and biofouling are common problems for facilities and equipment in the marine environment, and organic coatings have become one of the most important anti-corrosion and anti-fouling methods in the marine field. ZIF-8, as a zeolite imidazole framework structure material, exhibits good hydrophobicity, water stability and corrosion inhibition properties due to its high porosity, high surface area, high stability, and adjustable structure and function. Therefore, ZIF-8 is widely used in the modification of organic coatings. However, for the complex situation of biofouling in the ocean and microorganisms directly or indirectly promoting metal corrosion, the long-term protection of the metal substrate by the modified epoxy coating is still facing serious threats, and its protective effect is still unsatisfactory. Summary of the invention

[0003] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a functionalized ZIF-8 epoxy coating with antibacterial, antifouling and high corrosion resistance. The functionalized ZIF-8 epoxy coating has high corrosion resistance, can improve the antibacterial and antifouling performance of the coating in a marine environment, and can provide long-term protection for metal substrates, thereby solving the problem that the long-term protective effect of the modified epoxy coatings in the prior art on the metal substrates is poor.

[0004] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0005] A functionalized ZIF-8 epoxy coating with antibacterial, antifouling and high corrosion resistance, wherein the coating is prepared by the following method:

[0006] Step 1: zinc nitrate, dimethylimidazole, fluorinated graphene, an antibacterial agent and methanol are uniformly mixed to form a mixed solution, and the pH value of the mixed solution is adjusted to 5.8-6.8, the mixed solution is ultrasonically treated and then stirred, the product is collected by centrifugation for washing, and dried to obtain a functionalized ZIF-8 loaded on the surface of fluorinated graphene and encapsulating the antibacterial agent; wherein, in the mixed solution, the concentration of zinc nitrate is 0.1-3 g / L, the concentration of dimethylimidazole is 0.5-4 g / L, the concentration of fluorinated graphene is 0.1-2 g / L, and the concentration of the antibacterial agent is 0.2-2 g / L;

[0007] Step 2: Pre-treating the surface of the metal substrate;

[0008] Step 3: mixing the functionalized ZIF-8 prepared in step 1 with epoxy resin and diluent, stirring evenly by ball milling, adding curing agent and mixing evenly, thereby obtaining the functionalized ZIF-8 epoxy resin; wherein the mass ratio of the functionalized ZIF-8, epoxy resin and diluent is 10:(0.2-1):(1-8), and the amount of curing agent added is 40-50% of the mass of the epoxy resin;

[0009] Step 4: coating the functionalized ZIF-8 epoxy resin obtained in step 3 on the surface of the metal substrate treated in step 2, and forming the coating after drying and curing.

[0010] Preferably, the antibacterial agent is one or two of dodecylguanidine acetate, diammonium dihydrogen phosphate, 4,5-dichloro-N-octyl-4-isothiazoline-3-one, sulfamethoxam, dibromohydantoin, diquaternary ammonium salt, penthiopyrad, and polyhexamethyleneguanidine salt.

[0011] Preferably, in step 1, aqueous ammonia is used to adjust the pH value.

[0012] Preferably, in step 1, the fluorine content of the fluorinated graphene is calculated based on the fluorine-carbon ratio and is in the range of 15-60%, the average particle size is 0.3-6 μm, and the thickness is 1.5-8 nm.

[0013] Preferably, in step 3, the diluent is a mixture of xylene and n-butanol, and the mass ratio of xylene to n-butanol is (1.5-3):(1-2).

[0014] Preferably, in step 3, the curing agent is a polyamide curing agent.

[0015] Preferably, in step 4, the functionalized ZIF-8 epoxy resin is coated with a thickness of 50 to 180 μm.

[0016] Preferably, in step 2, the surface of the metal substrate is pretreated as follows:

[0017] The edge of the metal substrate is ground and sandblasted, then ultrasonically cleaned in an ethanol solution, and after cleaning and drying, it is soaked in an acetone solution and then set aside.

[0018] Preferably, in step 4, the drying and curing temperature is 45 to 110° C., and the curing time is 18 to 96 hours.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] 1. The present invention adopts functional ZIF-8 to significantly improve the hydrophobicity of epoxy resin, and utilizes the abundant organic ligands (such as imidazole) inside ZIF-8. These ligands can form a barrier on the surface of the coating to prevent the penetration of water molecules and other pollutants. In the marine environment, many microorganisms (such as algae and bacteria) rely on water and nutrients to survive and reproduce. The present invention enhances the hydrophobicity of the coating. ZIF-8 effectively reduces the residence time of water molecules on the surface of the coating, thereby reducing the chance of microbial attachment, thereby preventing the attachment of marine organisms, reducing biological fouling, and improving the antifouling performance of the coating.

[0021] 2. The present invention utilizes the porous structure of ZIF-8 to encapsulate the antibacterial agent. When the coating is corroded in the marine environment, the structure of ZIF-8 will gradually decompose. This decomposition process is not completed instantly, but is a slow and gradual process. During this process, the metal ions (such as zinc ions) released after the decomposition of ZIF-8 can react with the corrosive medium to form a protective passivation film to prevent further corrosion. At the same time, the slow decomposition of ZIF-8 will trigger the release of the antibacterial agent, but due to the small pore size of ZIF-8, the release rate of the antibacterial agent is relatively slow, which ensures that the antibacterial agent can remain active for a long time and continue to resist the invasion of microorganisms. In this way, ZIF-8 not only provides a physical barrier for the coating, but also enhances its protective ability at the chemical level, ensuring the long-term stability and reliability of the coating in a complex marine environment.

[0022] 3. The present invention uses fluorinated graphene to load ZIF-8, because the CF bond in fluorinated graphene has extremely high bond energy, which makes it show excellent stability in high temperature and strong chemical environment. This stability enables fluorinated graphene to withstand extreme conditions in the marine environment, such as high salinity, high humidity and fluctuating temperature, without degradation or performance loss. At the same time, the insulating properties of fluorinated graphene also prevent the occurrence of electrochemical corrosion, further enhancing the corrosion resistance of the coating; at the same time, after loading ZIF-8 with fluorinated graphene, a unique large-surface-area nanosheet structure is formed, which can extend the penetration path of the corrosive medium and slow down the speed at which the corrosive medium reaches the metal matrix. Even if the coating in some areas is slightly damaged, the synergistic effect of fluorinated graphene and ZIF-8 can also repair the damaged parts to a certain extent, preventing the further expansion of corrosion and further improving the corrosion resistance of the coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The scanning electron microscope images of Example 1 and Comparative Examples 1 to 4 are shown; wherein a, b, c, d are Comparative Examples 1, 2, 3, 4; and e is Example 1.

[0024] Figure 2The low-frequency impedance modulus curves of the coatings prepared in Example 1 and Comparative Examples 1 to 4 are shown respectively.

[0025] Figure 3 These are comparison pictures of the contact angles of the coatings made in Example 1 and Comparative Examples 1 to 4, respectively; wherein a, b, c, d are Comparative Examples 1, 2, 3, 4; and e is Example 1.

[0026] Figure 4 The antibacterial microscopic morphology pictures and EDS spectrum comparison results of the coatings of Example 1 and Comparative Example 2; wherein a is Comparative Example 2, and b is Example 1. DETAILED DESCRIPTION

[0027] The present invention will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the present invention belong to the scope of protection of the present invention.

[0028] Unless otherwise indicated in specific cases in the present invention, the numerical ranges listed herein include the upper and lower limits, and all integers and fractions within the range, and are not limited to the specific values ​​listed when defining the range.

[0029] 1. A functionalized ZIF-8 epoxy coating with antibacterial, antifouling and high corrosion resistance

[0030] Step 1: zinc nitrate, dimethylimidazole, fluorinated graphene, an antibacterial agent and methanol are uniformly mixed to form a mixed solution, and the pH value of the mixed solution is adjusted to 5.8-6.8, the mixed solution is ultrasonically treated and then stirred, the product is collected by centrifugation for washing, and dried to obtain a functionalized ZIF-8 loaded on the surface of fluorinated graphene and encapsulating the antibacterial agent; wherein, in the mixed solution, the concentration of zinc nitrate is 0.1-3 g / L, the concentration of dimethylimidazole is 0.5-4 g / L, the concentration of fluorinated graphene is 0.1-2 g / L, and the concentration of the antibacterial agent is 0.2-2 g / L;

[0031] Step 2: Pre-treating the surface of the metal substrate;

[0032] Step 3: mixing the functionalized ZIF-8 prepared in step 1 with epoxy resin and diluent, stirring evenly by ball milling, adding curing agent and mixing evenly, thereby obtaining the functionalized ZIF-8 epoxy resin; wherein the mass ratio of the functionalized ZIF-8, epoxy resin and diluent is 10:(0.2-1):(1-8), and the amount of curing agent added is 40-50% of the mass of the epoxy resin;

[0033] Step 4: coating the functionalized ZIF-8 epoxy resin obtained in step 3 on the surface of the metal substrate treated in step 2, and forming the coating after drying and curing.

[0034] The present invention takes into account the problems existing in the prior art, and selects ZIF-8 as a carrier of the antibacterial agent among many ZIF materials. ZIF-7 is not as good as ZIF-8 in the coating effect of the antibacterial agent. The porous structure of ZIF-8 is used to encapsulate the antibacterial agent. Even in an acidic or alkaline environment, when ZIF-8 is corroded and decomposed, this decomposition process is not completed instantly, but a slow and gradual process. In this process, the metal ions (such as zinc ions) released after the decomposition of ZIF-8 can react with the corrosive medium to form a protective passivation film to prevent further corrosion; at the same time, the decomposition of ZIF-8 triggers the release of the antibacterial agent, but due to the small pore size of ZIF-8, the release rate of the antibacterial agent is relatively slow, which ensures that the antibacterial agent can remain active for a long time and continuously resist the invasion of microorganisms. In this way, ZIF-8 not only provides a physical barrier for the coating, but also enhances its protective ability at the chemical level, ensuring the long-term stability and reliability of the coating in a complex marine environment. The present invention also uses fluorinated graphene as a carrier. Compared with ordinary graphene, fluorinated graphene has excellent thermal stability, chemical stability and excellent insulation performance due to its various types of CF bonds and CC bonds from sp2 to sp3 structural transformation. After loading ZIF-8, a unique large-surface-area nanosheet structure is formed, which can extend the penetration path of the corrosive medium and slow down the speed at which the corrosive medium reaches the metal matrix. Even if the coating in some areas is slightly damaged, the synergistic effect of fluorinated graphene and ZIF-8 can repair the damaged parts to a certain extent, prevent the further expansion of corrosion, and further improve the corrosion resistance of the coating.

[0035] In some embodiments of the present invention, in the mixed solution described in step 1, the concentrations of zinc nitrate, dimethylimidazole, fluorinated graphene and antibacterial agent are controlled within the range, which can ensure the formation of enough ZIF-8 to encapsulate the antibacterial agent on the one hand, avoiding the situation that the amount of ZIF-8 is not enough to encapsulate enough antibacterial agent, and on the other hand, it can also avoid the situation that the amount of generated ZIF-8 is too much, which leads to poor encapsulation effect. Therefore, the concentration of zinc nitrate can be 0.1g / L, 1g / L, 2g / L, 3g / L, etc., and all ranges and sub-ranges between the above values; the concentration of dimethylimidazole can be 0.5g / L, 1g / L, 2g / L, 3g / L, 4g / L, etc., and all ranges and sub-ranges between the above values; the concentration of fluorinated graphene can be 0.1g / L, 1g / L, 2g / L, and the concentration of the antibacterial agent can be 0.2g / L, 1g / L, 2g / L, etc., and all ranges and sub-ranges between the above values. It should be understood that in embodiments, any of the above ranges may be combined with any other ranges.

[0036] In some embodiments of the present invention, the antibacterial agent is one or two of dodecylguanidine acetate, ammonium dihydrogen phosphate, 4,5-dichloro-N-octyl-4-isothiazoline-3-one, sulfamethoxazole, dibromohydantoin, diquaternary ammonium salt, penthiopyrad, and polyhexamethyleneguanidine salt. The types of antibacterial agents coated with ZIF-8 should not be too many. If more than two types are used, the coating effect will be affected, and the antibacterial performance will be reduced. Therefore, the types of antibacterial agents should not exceed two.

[0037] In some embodiments of the present invention, ammonia water is used to adjust the pH value in step 1. Ammonia water is an alkaline organic compound, which can not only adjust the pH value of the mixed solution to make the solution properties more stable, but also the elements contained in ammonia water will not have an adverse effect on the synthesis of functionalized ZIF-8.

[0038] In some embodiments of the present invention, in step 1, the fluorine content of fluorinated graphene is calculated based on the fluorine-carbon ratio, the average particle size of fluorinated graphene is 0.3-6 μm, and the thickness of fluorinated graphene is 1.5-8 nm. In the present invention, the fluorine content of fluorinated graphene should reach 15% to 60%, which is conducive to ensuring that the modified coating has strong hydrophobicity and high stability. Lower or higher than this fluorine content will lead to a reduction in the surface active sites of fluorinated graphene, affecting the load of ZIF-8. According to the standard GB / T41067-2021, it is detected to ensure that the fluorinated graphene contains enough fluorine elements, so the fluorine content of fluorinated graphene can be 15%, 20%, 30%, 40%, 50%, 60%, etc., as well as all ranges and sub-ranges between the above values. The thickness of fluorinated graphene also needs to be controlled to ensure the characteristics of the fluorinated graphene lamella structure, so as to give full play to its lamella structure to form a "maze effect" during the service of the coating, and increase the diffusion path of the corrosive medium inside the coating. Therefore, the thickness of fluorinated graphene can be 1.5nm, 2nm, 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, etc., as well as all ranges and sub-ranges between the above values. In addition, the average particle size of fluorinated graphene also needs to be controlled, because if the size is too small, the advantages of the lamella structure of fluorinated graphene are difficult to highlight and cannot play a "maze effect"; while if the size is too large, the dispersibility of fluorinated graphene inside the coating is affected, and the corrosion resistance of the coating is ultimately affected. Therefore, the average particle size of fluorinated graphene can be 0.3μm, 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, etc., as well as all ranges and sub-ranges between the above values. It should be understood that in the embodiment, any of the above ranges can be combined with any other ranges.

[0039] In some embodiments of the present invention, in step 3, the diluent is a mixture of xylene and n-butanol, and the mass ratio of xylene to n-butanol can be 1.5:1, 1.5:2, 2:1.5, 3:2, 3:1, etc., and all ranges and sub-ranges between the above values. It should be understood that in embodiments, any of the above ranges can be combined with any other ranges.

[0040] In some embodiments of the present invention, in step 3, the curing agent is a polyamide curing agent.

[0041] In some embodiments of the present invention, in step 4, the functionalized ZIF-8 epoxy resin is coated with a thickness of 50 to 180 μm.

[0042] In some embodiments of the present invention, in step 2, the surface of the metal substrate is pretreated as follows:

[0043] The edge of the metal substrate is ground and sandblasted, then ultrasonically cleaned in an ethanol solution, and after cleaning and drying, it is soaked in an acetone solution and then set aside.

[0044] In some embodiments of the present invention, in step 4, the drying and curing temperature is 45 to 110° C., and the curing time is 18 to 96 hours.

[0045] 2. Examples and Comparative Examples

[0046] Example 1

[0047] (1) Preparation of functionalized ZIF-8 filler: First, 0.18 g of fluorinated graphene with a fluorine content of 18.54% was added to 250 ml of methanol solution, and ultrasonically dispersed for 2 h. Then, 0.3 g of zinc nitrate, 1.1 g of dimethylimidazole, and 2 g of 4,5-dichloro-N-octyl-4-isothiazoline-3-one were added and stirred evenly. Then, ammonia acid was added dropwise to adjust the pH value of the solution to 6.5. After stirring at room temperature for 30 minutes, the product was collected by centrifugation, and the product was alternately washed with deionized water and methanol. Finally, it was freeze-dried to obtain functionalized ZIF-8 loaded on the surface of fluorinated graphene and encapsulated with the antibacterial agent;

[0048] (2) Pretreatment of the metal substrate: grind the edge of the metal substrate, sandblast it, put it into an ethanol solution for ultrasonic cleaning, and then soak it in an acetone solution after cleaning and drying;

[0049] (3) Preparation of functionalized ZIF-8 epoxy resin: epoxy resin, functionalized ZIF-8 and diluent were mixed in a mass ratio of 10:0.3:4, wherein the diluent was xylene and n-butanol, which were mixed in a mass ratio of 3:2, and ball milled for 2 h. For every 80 g of epoxy resin E-44, 60 g of polyamide 651 curing agent was added, stirred for 10 min, and vacuumed to obtain functionalized ZIF-8 epoxy resin;

[0050] (4) Coating: The surface of the metal substrate obtained in step (2) is coated with a functionalized ZIF-8 epoxy resin with a thickness of 110±10 um, and then cured at 45-60° C. for 72 h to obtain a functionalized ZIF-8 epoxy coating.

[0051] Example 2

[0052] (1) Preparation of functionalized ZIF-8 filler: First, 0.15 g of fluorinated graphene was added to 220 ml of methanol solution, and ultrasonic dispersion was performed for 2 h. Then, 0.26 g of zinc nitrate, 1.03 g of dimethylimidazole, and 0.5 g of dibromohydantoin were added and stirred evenly. Then, ammonia acid was added dropwise to adjust the pH value of the solution to 6.2. After stirring at room temperature for 30 min, the product was collected by centrifugation, and the product was alternately washed with deionized water and methanol. Finally, freeze-dried to obtain functionalized ZIF-8 loaded on the surface of fluorinated graphene and encapsulating the antibacterial agent;

[0053] (2) Pretreatment of the metal substrate: grind the edge of the metal substrate, sandblast it, put it into an ethanol solution for ultrasonic cleaning, and then soak it in an acetone solution after cleaning and drying;

[0054] (3) Preparation of functionalized ZIF-8 epoxy resin: epoxy resin, functionalized ZIF-8 and diluent were mixed in a mass ratio of 10:0.3:3, wherein the diluent was xylene and n-butanol, which were mixed in a mass ratio of 3:2, and ball milled for 2 h. For every 80 g of epoxy resin E-44, 50 g of polyamide 650 curing agent was added, stirred for 10 min, and vacuumed to obtain functionalized ZIF-8 epoxy resin;

[0055] (4) Coating: The surface of the metal substrate obtained in step (2) is coated with a functionalized ZIF-8 epoxy resin with a thickness of 110±10 um, and then cured at 45-60° C. for 72 h to obtain a functionalized ZIF-8 epoxy coating.

[0056] Example 3

[0057] (1) Preparation of functionalized ZIF-8 filler: First, 0.2 g of fluorinated graphene was added to 260 ml of methanol solution, and ultrasonic dispersion was performed for 2 h. Then, 0.33 g of zinc nitrate, 1.24 g of dimethylimidazole, and 1.5 g of diquaternary ammonium salt were added and stirred evenly. Then, ammonia acid was added dropwise to adjust the pH value of the solution to 6.4. After stirring at room temperature for 30 min, the product was collected by centrifugation, and the product was alternately washed with deionized water and methanol. Finally, freeze-dried to obtain functionalized ZIF-8 loaded on the surface of fluorinated graphene and encapsulated with the antibacterial agent;

[0058] (2) Pretreatment of the metal substrate: grind the edge of the metal substrate, sandblast it, put it into an ethanol solution for ultrasonic cleaning, and then soak it in an acetone solution after cleaning and drying;

[0059] (3) Preparation of functionalized ZIF-8 epoxy resin: epoxy resin, functionalized ZIF-8 and diluent were mixed in a mass ratio of 10:0.5:6, wherein the diluent was xylene and n-butanol, which were mixed in a mass ratio of 3:2, and ball milled for 2 h. For every 80 g of epoxy resin E-41, 56.5 g of polyamide 651 curing agent was added, stirred for 10 min, and vacuumed to obtain functionalized ZIF-8 epoxy resin;

[0060] (4) Coating: The surface of the metal substrate obtained in step (2) is coated with a functionalized ZIF-8 epoxy resin with a thickness of 110±10 um, and then cured at 45-60° C. for 72 h to obtain a functionalized ZIF-8 epoxy coating.

[0061] Example 4

[0062] An improvement is made on the basis of Example 1, the difference being that the fluorine content in the adopted fluorinated graphene is 15%, and the other steps are completely consistent with Example 1.

[0063] Example 5

[0064] An improvement is made on the basis of Example 1, the difference being that the fluorine content in the adopted fluorinated graphene is 60%, and the other steps are completely consistent with Example 1.

[0065] Comparative Example 1

[0066] (1) Preparation of ZIF-7 filler: First, 0.21 g zinc nitrate and 1.33 g benzimidazole were added to 260 ml methanol. After fully dissolved, the mixture was stirred in a water bath at 60° for 1 h. The product was then collected by centrifugation. The product was washed alternately with deionized water and methanol, and finally freeze-dried to obtain ZIF-7.

[0067] (2) Pretreatment of the metal substrate: grind the edge of the metal substrate, sandblast it, put it into an ethanol solution for ultrasonic cleaning, and then soak it in an acetone solution after cleaning and drying;

[0068] (3) Preparation of ZIF-7 epoxy resin: epoxy resin, ZIF-7 and diluent were mixed in a mass ratio of 10:0.3:4, wherein the diluent was xylene and n-butanol, which were mixed in a mass ratio of 3:2, and ball milled for 2 h. For every 80 g of epoxy resin E-44, 60 g of polyamide 651 curing agent was added, stirred for 10 min, and vacuumed to obtain ZIF-7 epoxy resin;

[0069] (4) Coating: The surface of the metal substrate obtained in step (2) is coated with ZIF-7 epoxy resin with a thickness of 110±10 μm, and then cured at 45-60° C. for 72 h to obtain a ZIF-7 epoxy coating.

[0070] Comparative Example 2

[0071] An improvement is made on the basis of Example 1, except that no fluorinated graphene and antibacterial agent are added, and other steps are completely consistent with Example 1.

[0072] Comparative Example 3

[0073] An improvement is made on the basis of Example 1, the difference being that ordinary graphene is used, and the other steps are completely consistent with Example 1.

[0074] Comparative Example 4

[0075] Improvements were made on the basis of Example 1, except that: the ZIF-7 prepared in Comparative Example 1 was mixed with fluorinated graphene to obtain a ZIF-7 fluorinated graphene epoxy coating, and the other steps were completely consistent with Example 1.

[0076] 3. Performance Comparison

[0077] 1. Microscopic morphology observation

[0078] Taking Example 1 and Comparative Examples 1 to 4 as examples, the microscopic morphology of the four fillers was observed using a scanning electron microscope. Figure 1 As shown, the microscopic morphology of Comparative Examples 1 and 2 is as follows Figure 1 As shown in (a) and (b), ZIF-7 and ZIF-8 have clear shapes and relatively uniform sizes; the microscopic morphology of comparative example 3 is as follows Figure 1 As shown in (c), the size of ZIF-8 is significantly reduced, and agglomeration occurs on the graphene surface, which indicates that the loading of ZIF-8 on the surface of ordinary graphene is worse than that of fluorinated graphene, and agglomeration occurs more easily. The microscopic morphology of Comparative Example 4 is as follows Figure 1 As shown in (d), the size of ZIF-7 is significantly reduced and the distribution is relatively uniform, but there is still a very obvious agglomeration phenomenon; the microscopic morphology of Example 1 is as follows Figure 1 As shown in (d), the size of ZIF-8 is significantly reduced, the number is increased, and it is evenly distributed on the surface of fluorinated graphene, indicating that ZIF-8 is successfully loaded on fluorinated graphene.

[0079] 2. Electrochemical impedance spectroscopy experiment

[0080] Taking Example 1 and Comparative Examples 1 to 4 as examples, the cured epoxy coating was subjected to electrochemical impedance spectroscopy test in a 3.5wt% NaCl solution. After 4000h of testing, the low-frequency impedance modulus curve is as follows: Figure 2 The coating of Example 1 has the highest impedance value under long-term conditions, and the low-frequency impedance modulus is always maintained at 10 11 ~10 12 Ω·cm 2 , far higher than all the comparative examples. Among the comparative examples, the one closest to Example 1 is Comparative Example 4. However, as time goes by, the gap between the corrosion resistance of Comparative Example 4 and that of Example 1 gradually increases, which shows that even if ZIF-7 is combined with fluorinated graphene, the corrosion resistance improvement it brings is still not as good as that of ZIF-8; secondly, the corrosion resistance of Comparative Example 3 has decreased exponentially compared with that of Example 1, but both are much higher than Comparative Examples 1 and 2, which shows that ordinary graphene is not as good as fluorinated graphene in improving the corrosion resistance of the coating. At the same time, ZIF-8 is worse than ZIF-7 in improving the corrosion resistance of the coating. The long-term low-frequency impedance modulus of the functionalized ZIF-8 epoxy coating of Examples 2 to 5 can also be maintained at 10 11 ~10 12 Ω·cm 2 , indicating that the functionalized ZIF-8 epoxy coating loaded on the surface of fluorinated graphene has better corrosion resistance.

[0081] 3. Hydrophobic contact angle experiment

[0082] Taking Example 1 and Comparative Examples 1 to 4 as examples, the cured epoxy coating was placed flat on an automatic tilt contact angle measuring instrument to obtain the contact angle test results as shown in the figure. Figure 3 As shown, the experimental results of Comparative Examples 1 to 4 are as follows Figure 3 As shown in (a)(b)(c)(d), the contact angle of its epoxy coating is gradually increasing. This shows that the hydrophobicity of Comparative Example 2 (ZIF-8 epoxy coating) is better than that of Comparative Example 1 (ZIF-7 epoxy coating). At the same time, the introduction of ordinary graphene can improve the hydrophobicity of ZIF-8 epoxy coating to a certain extent, but ordinary graphene is not as good as fluorinated graphene for the improvement effect of hydrophobicity. Moreover, ZIF-7 is not as good as ZIF-8 for the improvement effect of hydrophobicity. The experimental results of Example 1 are shown in Figure 3 As shown in (e), the contact angle of the functionalized ZIF-8 epoxy coating is 115.23°; it can be seen that after being loaded on the fluorinated graphene surface, the hydrophobicity of the epoxy coating is improved to a certain extent by the functionalized ZIF-8, and the contact angle is increased from 103.41° to 115.23°.

[0083] 4. Antibacterial test

[0084] Taking Example 1 and Comparative Example 2 as examples, the ZIF-8 epoxy coating was immersed in bacterial culture solution for 720 hours for antibacterial testing. The surface micromorphology and EDS spectrum analysis results of the coating are shown in Figure 2. Figure 4 The experimental results of Comparative Example 2 are shown in Figure 4 As shown in (a), there are a large number of bacteria on the surface of the ZIF-8 epoxy coating, and the S and Fe elements in the EDS spectrum are relatively high, indicating that there are more corrosion products such as sulfides and iron oxides on the coating surface; the experimental results of Example 1 are as follows Figure 4 As shown in (b), the bacteria on the surface of the functionalized ZIF-8 epoxy coating are significantly reduced, and the content of S and Fe in the EDS spectrum is reduced, indicating that the corrosion products such as sulfide and iron oxide on the coating surface are reduced. The above analysis proves that the functionalized ZIF-8 epoxy coating loaded with antibacterial agent has better antibacterial properties.

[0085] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the technical solution. Those skilled in the art should understand that those modifications or equivalent substitutions of the technical solution of the present invention that do not depart from the purpose and scope of the technical solution should be included in the scope of the claims of the present invention.

Claims

1. A functionalized ZIF-8 epoxy coating with antibacterial, antifouling and high corrosion resistance, characterized in that: The coating is prepared by the following method: Step 1: zinc nitrate, dimethylimidazole, fluorinated graphene, an antibacterial agent and methanol are uniformly mixed to form a mixed solution, and the pH value of the mixed solution is adjusted to 5.8-6.8, the mixed solution is ultrasonically treated and then stirred, the product is collected by centrifugation for washing, and dried to obtain a functionalized ZIF-8 loaded on the surface of fluorinated graphene and encapsulating the antibacterial agent; wherein, in the mixed solution, the concentration of zinc nitrate is 0.1-3 g / L, the concentration of dimethylimidazole is 0.5-4 g / L, the concentration of fluorinated graphene is 0.1-2 g / L, and the concentration of the antibacterial agent is 0.2-2 g / L; Step 2: Pre-treating the surface of the metal substrate; Step 3: mixing the functionalized ZIF-8 prepared in step 1 with epoxy resin and diluent, stirring evenly by ball milling, adding a curing agent and mixing evenly to obtain the functionalized ZIF-8 epoxy resin; wherein the mass ratio of the functionalized ZIF-8, epoxy resin and diluent is 10:(0.2-1):(1-8), and the amount of the curing agent added is 40%-50% of the mass of the epoxy resin; Step 4: coating the functionalized ZIF-8 epoxy resin obtained in step 3 on the surface of the metal substrate treated in step 2, and forming the coating after drying and curing.

2. The functionalized ZIF-8 epoxy coating according to claim 1, characterized in that: The antibacterial agent is one or two of dodecylguanidine acetate, ammonium dihydrogen phosphate, 4,5-dichloro-N-octyl-4-isothiazoline-3-one, sulfamethoxam, dibromohydantoin, diquaternary ammonium salt, penthiopyrad, and polyhexamethyleneguanidine salt.

3. The functionalized ZIF-8 epoxy coating according to claim 1, characterized in that: In step 1, the pH value is adjusted using aqueous ammonia.

4. The functionalized ZIF-8 epoxy coating according to claim 1, characterized in that: In step 1, the fluorine content of the fluorinated graphene is calculated based on the fluorine-carbon ratio, ranging from 15 to 60%, the average particle size is 0.3 to 6 μm, and the thickness is 1.5 to 8 nm.

5. The functionalized ZIF-8 epoxy coating according to claim 1, characterized in that: In step 3, the diluent is a mixture of xylene and n-butanol, and the mass ratio of xylene to n-butanol is (1.5-3):(1-2).

6. The functionalized ZIF-8 epoxy coating according to claim 1, characterized in that: In step 3, the curing agent is a polyamide curing agent.

7. The functionalized ZIF-8 epoxy coating according to claim 1, characterized in that: In step 4, a functionalized ZIF-8 epoxy resin is coated with a thickness of 50 to 180 μm.

8. The functionalized ZIF-8 epoxy coating according to claim 1, characterized in that: In step 2, the metal substrate surface is pretreated as follows: The edge of the metal substrate is ground and sandblasted, then ultrasonically cleaned in an ethanol solution, and after cleaning and drying, it is soaked in an acetone solution and then set aside.

9. The functionalized ZIF-8 epoxy coating according to claim 1, characterized in that: In step 4, the drying and curing temperature is 45 to 110° C., and the curing time is 18 to 96 hours.

Citation Information

Patent Citations

  • Preparation method of high-corrosion-resistance modified epoxy resin composite coating

    CN112341900A

  • Sulfate reducing bacteria metabolism microenvironment response type composite coating and preparation method thereof

    CN113462215A

  • Antibacterial and anticorrosive difunctional powder as well as preparation method and application thereof

    CN116554495A